2020
DOI: 10.15177/seefor.20-19
|View full text |Cite
|
Sign up to set email alerts
|

Who Are the Visitors of Forest Park Grmoščica and What Are Their Needs? Results of Quantitative Exploratory Survey

Abstract: Forest Park Grmoščica is an important part of urban green infrastructure for the citizens of the western part of the city of Zagreb. To enhance the quality of management of the forest park to the satisfaction of its daily users, it is important to know their socio-demographic characteristics, visiting behaviour, recreational activities, as well as their perception of the forest park. The survey for users of the Forest Park Grmoščica was developed within the INTERREG DANUBE’s URBforDAN project. It was filled ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Although the perceived amount of litter, illegal littering, irresponsible visitor behaviour, visitor control and poor behaviour of other users were less frequently cited, these dissatisfactions can have a significant impact on the quality of time spent in green spaces (Ciesielski and Stereńczak 2018). Problems related to litter such as illegal littering or lack of bins, the need for additional equipment essential for spending time in green spaces, and dissatisfaction with the behaviour of other users of green spaces were frequently expressed as problems in a recent survey of visitors in one of Zagreb's forest parks (Krajter Ostoić et al 2017, Kičić et al 2020. Research has shown that even a moderate amount of litter can elicit a reaction from green space users (Verlič et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Although the perceived amount of litter, illegal littering, irresponsible visitor behaviour, visitor control and poor behaviour of other users were less frequently cited, these dissatisfactions can have a significant impact on the quality of time spent in green spaces (Ciesielski and Stereńczak 2018). Problems related to litter such as illegal littering or lack of bins, the need for additional equipment essential for spending time in green spaces, and dissatisfaction with the behaviour of other users of green spaces were frequently expressed as problems in a recent survey of visitors in one of Zagreb's forest parks (Krajter Ostoić et al 2017, Kičić et al 2020. Research has shown that even a moderate amount of litter can elicit a reaction from green space users (Verlič et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Particular attention is paid to the forest recreation sector. Some explored the aesthetic preferences of users for different types of forest management (Paletto et al 2018), while others looked at visitor uses and urban forest conditions (Krajter Ostoić et al 2017, Kičić et al 2020). Specifically, these latest studies have increased over the course of the spread of the SARS-CoV-2 pandemic (Marin et al 2021).…”
Section: Participatory Management Of Nature-based Tourist Destinationsmentioning
confidence: 99%
“…The primary role of this questionnaire was not to serve scientific purposes (the project being not an academic project) but rather to help decision-makers and the project implementation team to understand the profile of the forest visitors. The questionnaire was developed by the main coordinator, the city of Ljubljana, and was implemented by every partner city, with local adaptations being allowed (Box 1) [see also Kičić et al (2020) for the publication of these information and data]. The questionnaire survey was implemented in 2018-2019 (Kičić et al, 2020).…”
Section: Objective 1: Assessing the Ecosystem Supply And Social Demand For Ecosystem Servicesmentioning
confidence: 99%
“…The questionnaire was developed by the main coordinator, the city of Ljubljana, and was implemented by every partner city, with local adaptations being allowed (Box 1) [see also Kičić et al (2020) for the publication of these information and data]. The questionnaire survey was implemented in 2018-2019 (Kičić et al, 2020). The questionnaire assessed the main activities for which the visitors visit the forest.…”
Section: Objective 1: Assessing the Ecosystem Supply And Social Demand For Ecosystem Servicesmentioning
confidence: 99%
See 1 more Smart Citation